Idala: An unnamed Function Peptide Vaccine for Tuberculosis - Ismail, Salmah; Darwish, N.T.; Teoh, T.C.; Abdulla, Mahmood Ameen; Omar, R. (Pharmacotherapy Group, University of Benin, Benin City, 2012)
Purpose: To evaluate Myt272 protein antigenicity and immunogenicity by trial vaccination in mice and its in silico analysis as a potential peptide vaccine for tuberculosis.